141. A preliminary study to evaluate the impact of calculation grid resolution and CT slice thickness on TPS calculated small fields OF. (December 2018) - Falco, M.D.; Clemente, S.; Fiandra, C.; Agostinelli, S.; Bagalà, P.; Benecchi, G.; Borzì, G.; Bresciani, S.; Broggi, S.; Carbonini, C.; Casale, M.; Casati, M.; et al.
Abstract: Purpose: Stereotactic Body Radiation Therapy (SBRT) for patients with early stage solid tumor is increasing thanks to modern technologies and integrated image-guided systems. A national study to evaluate the influence of calculation grid resolution and CT slice thickness on small fields calculated in an homogeneous phantom, is in progress. For this purpose, a preliminary investigation that collected different parameters on TPS management at Italian level, was performed. Methods: Twenty-eight centres of the Italian Association of Medical Physics (AIFM) SBRT working group were invited to fill out a questionnaire expressly prepared by expert Medical Physicists using Google Forms. Questions regarded: type of accelerator, MLC characteristics, CT images scan information, Treatment Planning System (TPS) type, strategy used for SBRT plans, small fields OF values, detector/detectors and set-up adopted for measurements. Results: Preliminary results from 28 centers show great heterogeneities. Most centers used LINACs with MLC width ⩽5 mm, 6MV and VMAT technique. 60% of centers used more than one detector to measure OFs and no corrective factor was adopted in small field data. 10 × 10 cm 2 field size was the normalization field. OF data inserted in TPS did not come from a multicenter OF measurements. 1 × 1 cm 2 was the smallest field size measured for 47% of centers. As for TPS, PB, CCC, MC, AAA and deteministic algorithms were used in 3%, 40%, 23%, 27% and 7% of centers, respectively. About 29% and 21 % of centers used 3 mm and 2 mm as CT slice thickness, respectively. 50% of centers used 2 mm calculation grid. Conclusions: The influence of the dose calculation resolution and CT slice thickness on small OFs has not been studied yet. This preliminary study, considered as the starting point, highlighted a great spread of answers of the participating center and could be used as a baseline for future investigations.